Review of Participatory Budgeting Practices in China - Ming Zhuang (Финансовый журнал)
This paper examines the development, implementation and challenges of participatory budgeting (PB) in various cities in China, including Beijing, Jiaozuo, Shenzhen and others. It explores the diverse origins, sustainability, depth, and breadth of citizen engagement in PB initiatives, as well as institutional and political factors influencing their effectiveness. The study highlights key challenges such as transparency and institutionalization of PB and its integration into existing governance structures. It also discusses the role of digital technologies in enhancing participatory processes, improving fiscal transparency and broadening citizen involvement. The paper concludes with a discussion on the future of PB in China, emphasizing the need for policy reforms, digital innovations and international comparative research to ensure its long-term viability and impact on public governance.